Caracterização florística e classificação vegetacional de um fragmento florestal urbano do oeste do Paraná - Silva, Jéssica Patrícia Borges da (2016)
The aim of this work was to define the vegetation type of the urban fragment 4 Parque Ecológico Paulo Gorski (PEPG) and evaluate the influences of the climate and 5 altitudinal environmental variables on the floristic composition. The total of 1332 6 arboreal individuals of circumference at breast height equal or greater than 15 cm, 7 totalizing 71 species, were sampled. In addition, 401 species from 12 works developed 8 in the Rainforest (RF), Deciduous Forest (DF), Semideciduous Forest (SF) and 9 Araucaria Forest (AF) from southern and southeastern Brazil were used to build a 10 matrix of relative abundance for the floristic similarity. The environmental variables 11 from PEPG and other fragments were extracted from WorldClim. The floristic 12 similarity was evaluated through a group analysis using Simpson's Paradox, and the 13 significance was evaluated through the similarity analysis. The environmental variables 14 were compared between groups through the one-way ANOVA test. The characteristic 15 species from each group were evaluated by a similarity percentage analysis. Three 16 coincidental groups were formed, with the following vegetation types: RF with 20% of 17 similarity, DF/SF with 39% and AF with 32%. Although the PEPG environmental 18 variables have shown themselves as intermediate between AF and DF/FS, this fragment 19 has grouped with other areas from AF.